2020
DOI: 10.1177/1071100720926123
|View full text |Cite
|
Sign up to set email alerts
|

Patient Characteristics of Possible Responders and Nonresponders to Total Ankle Arthroplasty

Abstract: Background: Characteristics of responders, or those who achieve a clinical improvement above the level of a minimal clinically important difference, have not been defined for total ankle arthroplasty (TAA). The purpose of this study was to determine patient characteristics that distinguish possible responders from possible nonresponders after TAA using criteria established for other arthroplasty surgeries. Methods: Patients undergoing TAA who were enrolled into a prospective study at a single academic center e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…Factors such as ipsilateral hindfoot fusion, rheumatoid disease, poor mental health, and peripheral vascular disease have been associated with poor outcomes following TAR. 3,6,23,24 Previous studies have demonstrated that patient-reported outcome measures (PROMs) may be useful in predicting who will achieve meaningful improvement after operative intervention for a variety of foot and ankle disorders. 2,11,18,25 PROMs may be employed preoperatively to evaluate the severity of patients' symptoms and counsel patients about the expected benefit of surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors such as ipsilateral hindfoot fusion, rheumatoid disease, poor mental health, and peripheral vascular disease have been associated with poor outcomes following TAR. 3,6,23,24 Previous studies have demonstrated that patient-reported outcome measures (PROMs) may be useful in predicting who will achieve meaningful improvement after operative intervention for a variety of foot and ankle disorders. 2,11,18,25 PROMs may be employed preoperatively to evaluate the severity of patients' symptoms and counsel patients about the expected benefit of surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Factors such as ipsilateral hindfoot fusion, rheumatoid disease, poor mental health, and peripheral vascular disease have been associated with poor outcomes following TAR. 3,6,23,24…”
Section: Introductionmentioning
confidence: 99%
“…All the necessary data were retrieved from the studies that ascertained the correlation between mental health disorders and postoperative outcomes and complications. Three of the included studies were prospective studies [22][23][24] and the other four were retrospective studies [25][26][27][28] . The level of evidence (II and III) was reported for the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Mental health conditions included within the articles were depression [22][23][24][25][26][27][28] , schizophrenia 28 , bipolar disorder 28 and overall mental health 27 . The prevalence of depression ranged from 11.4-32.5% [22][23][24][25] (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, 9 studies with a total of 10 388 patients were eligible for inclusion in the quantitative analysis [6][7][8]15,16,26,53,62,64 and 28 in the narrative synthesis. [1][2][3][4][5][9][10][11]13,14,[17][18][19]23,25,29,[34][35][36]40,44,47,48,50,51,56,59,65…”
Section: Search and Selectionmentioning
confidence: 99%